2011
DOI: 10.1007/s10804-011-9127-x
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness in Younger, Middle-Aged and Older Adults: Age and Gender Matters

Abstract: The present study investigated age and gender differences in forgiveness of real-life transgressions. Emerging and young, middle-aged, and older adults recalled the most recent and serious interpersonal transgression and then completed the Transgression-Related Interpersonal Motivations Inventory (TRIM-18), which measured their avoidance, revenge, and benevolence motivation toward an offender and indicated to what extent they are generally concerned with the subject of forgiveness. The results revealed a trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 51 publications
4
36
2
9
Order By: Relevance
“…Sixth, the majority of the research found in the current review involved samples from the United States with the exception of Rangganadhan and Todorov (2010) and Ghaemmaghami et al (2011). Although past meta-analytic research did not find culture as a significant moderator in the sex and forgiveness literature (e.g., , cultural variables still may be important in the sex, forgiveness, and health relationship.…”
Section: Limitations Of Current Researchmentioning
confidence: 84%
See 2 more Smart Citations
“…Sixth, the majority of the research found in the current review involved samples from the United States with the exception of Rangganadhan and Todorov (2010) and Ghaemmaghami et al (2011). Although past meta-analytic research did not find culture as a significant moderator in the sex and forgiveness literature (e.g., , cultural variables still may be important in the sex, forgiveness, and health relationship.…”
Section: Limitations Of Current Researchmentioning
confidence: 84%
“…Ghaemmaghami, Allemand, and Martin (2011) examined state forgiveness across various age groups. Furthermore, variables such as transgression and age may be moderators of the sex effect in the forgiveness-health relationship.…”
Section: Sex Salience and Age Differences In Forgiveness And Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some authors (Allemand, 2008;Ghaemmaghami, Allemand, & Martin, 2011;Steiner, Allemand, & McCullough, 2012) indicate that older people tend to have a greater ability to forgive than do younger people, contradicting hypothesis 5. This can be a result of older individuals' greater experience with interpersonal problems and transgressions over the course of their lives , leading people with more experience to concentrate on more signifi cant emotional aspects, such as the maintenance of relationships, allowing them to grant their offender forgiveness more easily (Lang & Carstensen, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Não obstante, alguns autores (Allemand, 2008;Ghaemmaghami, Allemand, & Martin, 2011;Steiner, Allemand, & McCullough, 2012) pontuam que pessoas mais velhas tendem a apresentar uma maior habilidade de conceder o perdão do que aquelas mais jovens, contrapondo-se a hipótese 5. Isso aconteceria em decorrência das vivências, em maior número, de problemas interpessoais e transgressões ao longo da vida , levando as pessoas com mais experiência a direcionarem sua atenção a aspectos emocionais mais signifi cativos, como a manutenção de relacionamentos, concedendo assim, com maior facilidade o perdão ao seu ofensor (Lang & Carstensen, 2002).…”
Section: Discussionunclassified